Atmospheric Water Harvesting: A Review of Material and Structural Designs - Zhou, Xingyi; Lu, Hengyi; Zhao, Fei; Yu, Guihua (ACS materials letters, 2020)
Atmospheric water harvesting (AWH) emerges as a promising means to overcome the water scarcity of arid regions, especially for inland areas lacking liquid water sources. Beyond conventional system engineering that improves the water yield, novel moisture-harvesting materials provide new aspects to fundamentally promote the AWH technology benefiting from their high tunability and processability. Innovative material and structural designs enable the moisture harvesters with desirable features, such as high water uptake, facile water collection and long-term recyclability, boosting the rapid development of next-generation AWH. In this Perspective, we first illustrate the sorption mechanism, including absorption and adsorption for moisture-harvesting materials and summarize fundamental requirements, as well as design principles of moisture harvesters. Recent progress on material and structural designs of moisture harvesters for AWH is critically discussed. We conclude with prospective directions for next-generation moisture harvesters to promote AWH from scientific research to practical application.